Dietary habits and prostate cancer detection: a case–control study - Amin, Moamen; Jeyaganth, Suganthiny; Fahmy, Nader; Bégin, Louis R.; Aronson, Samuel; Jacobson, Stephen; Tanguay, Simon; Kassouf, Wassim; Aprikian, Armen (Canadian Urological Association Journal, 2013)
Background: Many studies have suggested that nutritional factors may affect prostate cancer development. The aim of our study was to evaluate the relationship between dietary habits and prostate cancer detection. Methods: We studied 917 patients who planned to have transrectal ultrasonography–guided prostatic biopsy based on an elevated serum prostate specific antigen (PSA) level, a rising serum PSA level or an abnormal digital rectal examination. Before receiving the results of their biopsy, all patients answered a self-administered food frequency questionnaire. In combination with pathology data we performed univariable and multivariable logistic regression analyses for the predictors of cancer and its aggressiveness. Results: Prostate cancer was found in 42% (386/917) of patients. The mean patient age was 64.5 (standard deviation [SD] 8.3) years and the mean serum PSA level for prostate cancer and benign cases, respectively, was 13.4 (SD 28.2) μg/L and 7.3 (SD 4.9) μg/L. Multivariable analysis revealed that a meat diet (e.g., red meat, ham, sausages) was associated with an increased risk of prostate cancer (odds ratio [OR] 2.91, 95% confidence interval [CI] 1.55–4.87, p = 0.027) and a fish diet was associated with less prostate cancer (OR 0.54, 95% CI 0.32–0.89, p = 0.017). Aggressive tumours were defined by Gleason score (≥ 7), serum PSA level (≥ 10 μg/L) and the number of positive cancer cores (≥ 3). None of the tested dietary components were found to be associated with prostate cancer aggressivity. Conclusion: Fish diets appear to be associated with less risk of prostate cancer detection, and meat diets appear to be associated with a 3-fold increased risk of prostate cancer. These observations add to the growing body of evidence suggesting a relationship between diet and prostate cancer risk.